Recommended Competencies Needed for Training in International Extension Settings - Robert Strong; Amy Harder (Journal of International Agricultural and Extension Education, 2011)
Agricultural extension plays a significant role in the global production and supply of food. A problem with extension services in developing countries is the lack of an adequate balance between the technical and professional competencies of personnel. The purpose of this study was to explore the professional competencies needed by U.S. extension agents to teach adults in international settings. The conceptual framework for this study was constructed on the knowledge domains that doctoral students should acquire before teaching internationally. Twelve internationally experienced U.S. extension agents were purposively selected to participate in the study based on their regional supervisor’s recommendation of program excellence. Change strategies, program evaluation methods, learning principles, and organizational development were identified by the agents as professional competencies needed before teaching internationally. Extension administrators and professional development specialists should ensure mechanisms are in place for current and future agricultural extension agents to acquire these competencies. U.S. agricultural extension agents could be mentored by agents proficient in the identified professional competencies before teaching globally. Enrolling in a doctoral program is an avenue for extension agents to acquire the professional competencies associated with teaching adults in international settings. Preparing current and future U.S. extension agents in the identified professional competencies could enhance global agricultural extension programs.
Keywords: professional competencies; agricultural extension agents; professional development